Management of Arabic Language Learning in Islamic Education: A Communicative Approach, Evaluation, and Quality Development in Islamic Education - Maria Ulfa; Fahrur Rosikh; Nasikhin Muad; A. Samsul Ma'arif; Muhamad Arif Mustofa (Mudir: Jurnal Manajemen Pendidikan, 2026)
Arabic language learning in Islamic religious universities faces challenges such as diverse initial student abilities, low levels of active participation, and the need to integrate a communicative approach with an Islamic context. This situation is further complicated in institutions located in Muslim minority areas, necessitating systematic and adaptive learning management innovations. This study aims to analyze Arabic language learning management innovations at the Jembrana Islamic School of Islamic Studies, Bali, encompassing aspects of learning planning, implementation, and evaluation. This study employed a descriptive qualitative approach with a case study design. Data were collected through observation, in-depth interviews with lecturers and students, and analysis of learning documents. Data were analyzed thematically to identify key patterns and findings related to learning innovation practices. The results indicate that Arabic language learning management encompasses learning planning conducted through student needs analysis, goal formulation based on a communicative approach, and the selection of student-centered learning strategies. Learning implementation integrates dialogue activities, conversation simulations, and project-based assignments that encourage active student involvement. Learning evaluation is conducted comprehensively, encompassing aspects of knowledge, attitudes, and skills, and is supported by lecturer reflection and student feedback as part of the process evaluation. Arabic language learning management at the Jembrana Islamic School of Education, Bali, demonstrates a systematic effort to improve the quality of learning. To support sustainable innovation, strengthening the use of digital media and managing learning time is necessary to ensure a more effective learning process that meets student needs.